Analysis of teacher training needs for peace education in early childhood education (PAUD) - Muhamad Kosim Gifari; Dinn Wahyudin (Inovasi Kurikulum, 2024)
In the Indonesian context, peace education is becoming increasingly relevant considering the existing cultural, religious, and ethnic diversity. Teachers are a critical sector and have a significant role in instilling peace education in schools. So, competent skills are needed by every teacher who teaches the students about peace education. Then, this study aims to analyze the need for teacher training in peace education in early childhood education. This study uses a quantitative method with a survey approach to explore the need for teacher training related to peace education in early childhood education (PAUD). Data collection was carried out using a Likert scale-based questionnaire. The population of this study is PAUD teachers of RA Al-Hikam Soreang in the Bandung Regency area. The research respondents were taken using the census technique.  The respondents were 5 (five) people or all teachers of RA Al-Hikam Soreang. This research reveals a significant need to improve teacher training in peace education in early childhood education. AbstrakDalam konteks Indonesia, pendidikan perdamaian menjadi semakin relevan mengingat keragaman budaya, agama, dan etnis yang ada. Guru adalah sektor yang sangat penting dan memiliki peran utama dalam menanamkan pendidikan perdamaian di sekolah. Sehingga diperlukan keterampilan yang kompeten untuk dimiliki oleh setiap guru yang akan mengajarkan kepada siswa tentang pendidikan perdamaian. Kemudian penelitian ini bertujuan untuk menganalisis perlunya pelatihan guru bagi pendidikan perdamaian pada pendidikan anak usia dini. Penelitian ini menggunakan metode kuantitatif dengan pendekatan survei untuk menganalisis kebutuhan pelatihan guru terkait pendidikan perdamaian di pendidikan anak usia dini (PAUD). Pengumpulan data dilakukan dengan menggunakan kuesioner berbasis skala Likert. Populasi penelitian ini adalah guru PAUD RA Al-Hikam Soreang di wilayah Kabupaten Bandung. Responden penelitian diambil dengan menggunakan teknik sensus. Jumlah responden yang diambil sebanyak 5 (lima) orang atau seluruh guru RA Al-Hikam Soreang. Penelitian ini mengungkapkan bahwa ada kebutuhan yang signifikan untuk meningkatkan pelatihan guru dalam pendidikan perdamaian di pendidikan anak usia dini.Kata Kunci: Pendidikan Anak Usia Dini (PAUD); pendidikan perdamaian; pelatihan guru